Real estate market and coffee legacy in Costa Rica: case of the metropolitan area of Heredia - Badilla Loría, Michael (2024)
Costa Rican history has a long relationship with coffee production, this has been part of the national identity, and for this reason its legacy is still present, in this case it is established as a symbol of well-being and ostentation in real estate market advertising. Therefore, it is proposed to analyze the transformation of urban morphology and the development of the real estate market in Heredia to identify the use of the coffee issue as an advertising attraction during 1980 and 2019. Content analysis of advertising images of the coffee product is carried out, and of two luxury residences in the Heredia area, called Tierras del Café and Vereda del Café, with bibliographic documentary support. A theoretical base is built that considers the imaginaries, to define the specifically coffee imaginary and the geographical imaginary; urbanism, to understand what urban morphology is, urban trees and advertising; and, finally, neoliberalism, which allows us to understand the opening of the real estate market, and nature -coffee trees- as merchandise. With all the above, it is evident that the coffee imaginary and nature are strongly used in the real estate market, as a way of attracting customers, through advertising.